Effects of different cooking methods and soil environment on the nutrition of Dioscorea opposita Thunb - Yun Zhang; Xinru Sun; Ang’ang Lu; Jianxia Lai; Yuran Yang; Jie Zhang; Abdelhadi E. L. Jaouhari; Jinhua Zhu; Fanyi Ma (npj Science of Food)
Abstract This study compared the effects of cooking processes (including steaming, boiling, hot-air roasting and microwaving) on the nutrients of Dioscorea opposita planting in sandy soil (SSCY) and loessial soil (LSCY). The contents of crude fiber and reducing sugar increased significantly during cooking for SSCY, whereas those of LSCY remained unchanged. A significant decline in allantoin content was observed in boiled yams (approximately 6.0% for SSCY and 14.1% for LSCY, respectively). Moreover, the differences in chemical compositions between SSCY and LSCY were compared using non-targeted metabolomics. Totally, 656 differential metabolites of LSCY were identified, including lipids, nucleotides, amino acids and derivatives, and organic acids, which might be the key reason why LSCY exhibits higher nutritional values than SSCY. This research contributed to understanding the systematic metabolic changes during planting and the molecular mechanisms influencing the quality formation, providing the theoretical references for the more scientific consumption of Chinese yam.